Analgesia for Children in Acute Pain in the Post-codeine Era - Poonai, Naveen; Zhu, Rongbu (Current Pediatric Reviews, 2018)
Background: Acute pain is one of the most common presenting complaints in pediatric patients presenting to the emergency department. Recently, concern about the safety of narcotics such as codeine has sparked a renewed interest in opioids such as morphine and intranasal fentanyl. Objectives: Consequently, opioids are being increasingly used in the clinical setting. Despite this, there is ample evidence that clinicians are less willing to offer opioids to children compared to adults. Methods: The reasons for this are multifactorial but nevertheless, the provision of adequate analgesia in children is echoed by a several academic societies as a priority for comprehensive care. To address this mandate, evidence for therapies such as oral morphine, topical analgesia, and intranasal fentanyl is now mounting. Result and Conclusions: This review will discuss the evidence and effectiveness of analgesia for children with acutely painful conditions in the post-codeine era.
Keywords: Morphine